Prognostic Significance of the Loss of Heterozygosity of KRAS in Early-Stage Lung Adenocarcinoma - Khadse, Anand; Haakensen, Vilde D.; Silwal-Pandit, Laxmi; Hamfjord, Julian; Micke, Patrick; Botling, Johan; Brustugun, Odd Terje; Lingjærde, Ole Christian; Helland, Åslaug; Kure, Elin H. (Frontiers in Oncology, 2022)
Lung cancer is a common disease with a poor prognosis. Genomic alterations involving the KRAS gene are common in lung carcinomas, although much is unknown about how different mutations, deletions and expressions influence the disease course. The first approval of a KRAS-directed inhibitor was recently approved by the FDA. Mutations in the KRAS gene have been found associated with poor prognosis for lung adenocarcinomas but implications of loss of heterozygosity (LOH) of KRAS have not been investigated. In this study, we have assessed the LOH of KRAS in early-stage lung adenocarcinoma by analyzing DNA copy number profiles and have investigated the effect on patient outcome in association with mRNA expression and somatic hotspot mutations. KRAS mutation was present in 36% of cases and was associated with elevated mRNA expression. LOH in KRAS was associated with favorable prognosis, more prominently in KRAS mutated than in wild type patients. The presence of both LOH and mutation in KRAS conferred a better prognosis than KRAS mutation alone. For wild type tumors no difference in prognosis was observed between patients with and without LOH in KRAS. Our study indicates that LOH in KRAS is an independent prognostic factor that may refine the existing prognostic groups of lung adenocarcinomas.